Investigating the impact of preslaughter handling intensity on goats: a study on behavior, physiology, blood enzymes, and hormonal responses - Al-Owaimer, Abdullah N.; Suliman, Gamaleldin M.; Alobre, Mohsen M.; Swelum, Ayman A.; Al-Badwi, Mohammed A.; Ba-Awadh, Hani; Sazili, Awis Qurni; Kumar, Pavan; Kaka, Ubedullah (Frontiers in Veterinary Science, 2024)
In this study, the effects of pre-slaughter handling on behavior, physiology, blood biochemistry, and hormonal responses in goats were assessed. Twenty-seven intact male goats of the Ardi breed were divided into a control group and two treatment groups with ear-pulling and leg-pulling groups. Goats in the treatment groups showed increased vocalization compared to the control group. Pre-slaughter handling intensity significantly influenced heart rate, respiration rate, rectal temperature, and ear temperature before and after handlingafterhandling. Glucose levels increased after handlingafter-handling, and the leg-pulling group had elevated lactate dehydrogenase levels post-handlingafter-handling. Catecholamine and β-endorphin concentrations also rose significantly after pre-slaughter handling. These results indicate that both ear and leg pulling negatively affect behavior, physiology, blood biochemistry, and hormonal responses in goats. Such stress can impact animal welfare and meat quality.Therefore, it is vital to follow animal welfare principles during pre-slaughter handling to minimize adverse effects. This study contributes valuable insights into the consequences of preslaughter stress in goats and highlights the importance of considering animal welfare in the livestock industry. By prioritizing the well-being of animals during handling and slaughter, we can improve meat quality and ethical standards, benefiting the community as a whole.